Evaluation of Methods of Gastroesophegeal Reflux Disease Diagnosis in Thawra Teaching Hospital Elbaida –Libya - Mohamed , Faraj Alhomry; Awami , Salem M.; Kharchevnyk, Mykhaylo (Al-Mukhtar Journal of Sciences, 2018)
Gastroesophageal reflux disease (GERD) results from the reflux of gastric contents, causing symptoms and injury to esophageal tissue. In this study, we evaluate methods of diagnosis of GERD and pattern of clinical, endoscopic, and histological findings in consecutive individuals. Patients were referred to endoscopy unit of Thawra Teaching Hospital, Elbaida-Libya for various reasons, they have Questionnaire-based assessment scales and were examined for the presence of reflux esophagitis, via endoscopy, and microscopic via histopathology. We had 48 patients with mean age of 45.5, 30 female, 18 male. Total patients with microscopic esophagitis were 29 (60.4%), and without microscopic esophagitis 19 (39.6%). The RDQ with a score of ≥ 8 as the diagnostic criteria of GERD, is not a conclusive diagnosis of GERD in isolation, but is of value in determining the need for further investigation. A normal endoscopy does not exclude GERD when endoscopy is inconclusive, adjunctive evidence from biopsy findings can add confidence for a GERD diagnosis. The finding of glandular mucosa without intestinal metaplasia in the distal 2 cm of the tubular esophagus is regarded as normal but indicates a much chronic acid exposure of the lower esophagus.